2019
DOI: 10.1108/jec-09-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Artistic orientation, financial literacy and entrepreneurial performance

Abstract: Purpose This study aims to examine the relationship between artistic orientation and entrepreneurial performance and how other central entrepreneurial resources, namely, entrepreneurial orientation and financial literacy, affect this relationship. Design/methodology/approach Regulatory focus theory was used to develop the model. A survey of 375 small creative business entrepreneurs was conducted in Yogyakarta, Indonesia, and a hierarchical linear regression was used for data analysis. Findings The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 95 publications
5
44
2
2
Order By: Relevance
“…The positive influence of financial literacy on sustainability is consistent with the results of Eniola and Entebang [20], who found that financial literacy had a direct, positive impact on the performance of Nigerian SMEs, and Purnomo [109], who also found that financial literacy had a direct impact on SMEs' performance. We identified financial literacy as an important component of organisations' intellectual capital and thus our findings are consistent with those of Carmeli and Tishler [31], who found that intellectual capital had a positive effect on SMEs' sustainability.…”
Section: Discussion Of the Findingssupporting
confidence: 87%
“…The positive influence of financial literacy on sustainability is consistent with the results of Eniola and Entebang [20], who found that financial literacy had a direct, positive impact on the performance of Nigerian SMEs, and Purnomo [109], who also found that financial literacy had a direct impact on SMEs' performance. We identified financial literacy as an important component of organisations' intellectual capital and thus our findings are consistent with those of Carmeli and Tishler [31], who found that intellectual capital had a positive effect on SMEs' sustainability.…”
Section: Discussion Of the Findingssupporting
confidence: 87%
“…For instance, we found that financial literacy significantly influences SMEs' performance in emerging economies. The findings relate to Purnomo, who pointed out that financially literate managers are capable of organizing resources that spur SMEs' performance. Moreover, Yang et al () also argued that financial literacy augments top managers understanding about markets and customers' demand that facilitate their performance and competitive advantage.…”
Section: Discussionmentioning
confidence: 63%
“…Particularly, in a creative and competitive atmosphere, top managers need to have adequate knowledge and skills of financial measures and financial concepts. Because financial knowledge enables managers to gain a favorable financial position in the markets (Purnomo, ). Education is very prominent for the searching and identification of new opportunities (Davidsson & Honig, ) because managers with sufficient knowledge management can make rational decisions and strategic planning during operational activities that improve the social performance of their ventures (Iqbal & Malik, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial literacy is very important particularly in small firms because the decision-making process of small firms is directly influenced owners and managers [ 50 ]. It significantly affects overall performance of creative ventures [ 51 ]. In SMEs sector, the role of financial literate managers is prominent for understanding customers’ needs and their necessities.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%